Efektivitas Pengobatan Massal Filariasis Setelah Empat Tahun Pengobatan Massal di Desa Ploso, Demak, Jawa Tengah - Monika Putri Solikah; Siwi Pramatama Mars Wijayanti; Lantip Rujito (BALABA: JURNAL LITBANG PENGENDALIAN PENYAKIT BERSUMBER BINATANG BANJARNEGARA, 2021)
TThe filariasis elimination program is carried out through mass treatment with Diethylcarbamazine Citrate (DEC) and albendazole once a year for five years. Filariasis mass treatment, which was carried out for five years, aims to reduce the prevalence rate of microfilaria < 1%. Evaluation of community treatment needs to be done, one of which is the Finger Blood Preparation (SDJ) and Polymerase Chain Reaction (PCR) methods. The purpose of this research was to know the effectiveness of mass treatment of filariasis after four years in Karang Ploso Village, Demak, Indonesia. This study is a descriptive study with a cross-sectional approach with a sample of 350 people. The study variables were an examination of SDJ microfilariae, PCR molecular examination, and interviews about filariasis knowledge. The examination methods used were SDJ and PCR. The data analysis used was univariate, microfilaria rate. The results of SDJ and PCR examinations were not found microfilariae, so that the Mf rate was 0%. As many as 97.4% of people adhered to taking medication, 91.1% of people had moderate knowledge of filariasis, 98.3% had an average experience of the Mass Drug Administration (MDA). The Mf rate results by SDJ and PCR in Demak after the fourth filariasis treatment program in 2019 was 0%. There was a decrease in SDJ results from 2016-2019, namely 1% to 0% in 2019.